Early detection of gastric cancer. - Hallissey, M T (1990)
OBJECTIVE--To see whether investigation of dyspeptic patients aged over 40 after their first consultation with the general practitioner would increase the proportions with early and operable gastric cancers. DESIGN--Prospective study of gastric cancer in dyspeptic patients aged over 40 from a defined population. SETTING--10 General practices (six in central Birmingham, four in Sandwell); the Queen Elizabeth Hospital, Birmingham; and Sandwell District General Hospital. PATIENTS--2659 Patients aged 40 or over referred with dyspepsia. MAIN OUTCOME MEASURE--Increase in early and operable gastric cancers detected in middle aged patients with dyspepsia. RESULTS--Disease was identified in 1992 patients (75%). Fifty seven were found to have gastric cancer, 36 being treated by potentially curative resection, including 15 with early cancer. CONCLUSIONS--The investigation of dyspeptic patients over 40 at first attendance can increase the proportion of early gastric cancers detected to 26% and the proportion of operable cases to 63%. Such a policy has the potential to reduce mortality from gastric cancer in the population.